Advertising and country-of-origin images as sources of brand equity and the moderating role of brand typicality - Loureiro, S. M. C.; Kaufmann, H. R. (Baltic Journal of Management, 2017)
Purpose: This research has two main purposes: (i) to explore the influence of an individual’s attitude towards advertising and country-of-origin images (brand origin and country of manufacture) on brand equity creation; and (ii) to investigate how brand typicality moderates the effect of brand origin macro image on perceived quality. Design/methodology/approach: The data to test the hypotheses were elicited from a consumer survey in the Greater Lisbon area (305 Portuguese consumers). The product category of smartphones was selected for two main reasons: (i) it has not been extensively analysed in previous studies on the subject of brand equity; (ii) it is a device well-known to Portuguese consumers (particularly in the Greater Lisbon area). Three criteria guided the selection of the brands. The first criterion is to select brands which are well-known to consumers. The second is to choose brands with a distinctive brand origin and a main country of manufacture. The third and final criterion is to consider brands in different positions in the brand ranking. In order to estimate structural path coefficients, R2, Q2, and Bootstrap techniques, the current study employs the Partial Least Squares (PLS) approach. Findings: The results show that individuals' attitudes towards advertisements have a positive impact on brand equity creation, whereas those towards the country of manufacture do not significantly influence brand equity creation. Attitudes towards brand origin only have a partial influence. Brand typicality, however, exerts a significant direct effect on brand equity dimensions and, hence, does not have a significant moderating effect. Research limitations/implications: The authors suggest analysing the influence of country-of-origin on dimensions of brand equity considering consumer segmentation, types of industry and a range of brands, as well as different levels of consumer involvement with the product category. Several brands with the same country-of-origin should be analysed in order to understand whether the effects on brand equity depend on the product category. Although the current study is a first attempt to combine the potential effect of individuals' attitudes towards advertisements and country-of-origin on creating brand equity, further research should examine additional potential antecedents of brand equity. Finally, cross-cultural studies are recommended. Practical implications: Regarding managerial implications, three main aspects should be taken into consideration. First, creative, original and different advertising strategies are more effective than the country-of-origin in creating brand equity and, consequently, in building loyalty among smartphone consumers. Secondly, consumers do not tend to care about the place, country or region where the smartphone is produced, but the image of the country where the brand originated may be important. Finally, managers should be aware that, at least, in the smartphone sector, the way consumers create favourable associations with the brand and typicality, trust the company and consider it good value for money, are more effective in building brand loyalty than the perceived quality of the product/brand. Social implications: Relating to the interrelationship between country-of-origin and brand equity, the results of the current study prove that the effects of country-of-origin are category specific. Therefore, more studies focused on other contexts of products and brands are still needed to know in more detail how country-of-origin exerts an influence on brand equity dimensions. Even within a product category context, the results can depend on individual brands being analysed. Originality/value: To the knowledge of the authors, this study is the first to investigate the dual (simultaneous) effect of individuals’ attitudes towards advertisements and country-of-origin images on brand equity dimensions. Adding to the originality of the paper, the category of smartphone with respect to brand equity has not been extensively analysed in previous studies.